Biomarkers and Redox Balance in Aging Rats after Dynamic and Isometric Resistance Training - Neves, Rodrigo Vanerson Passos; Rosa, Thiago dos Santos; Corrêa, Hugo Luca; da Silva Aires, Kethelen Mariana; Deus, Lysleine Alves; Sousa, Michel Kendy; Stone, Whitley Jo; Aguiar, Lana Ribeiro; Prestes, Jonato; Simões, Herbert Gustavo; Andrade, Rosângela Vieira; Moraes, Milton Rocha (International Journal of Sports Medicine, 2020)
Aging muscle is prone to sarcopenia and its associated telomere shortening and increased oxidative stress. Telomeres are protected by a shelterin protein complex, proteins expressed in response to DNA damage. Aerobic exercise training has shown to positively modulate these proteins while aging, but the effects of resistance training are less clear. This investigation was to examine the role of dynamic and isometric RT on markers of senescence and muscle apoptosis: checkpoint kinase 2, 53 kDa protein, shelterin telomere repeat binding 1 and 2, DNA repair, telomere length and redox state in the quadriceps muscle. Fifteen 49-week-old male rats were divided into three groups: control, dynamic resistance training, and isometric resistance training. Dynamic and isometric groups completed five sessions per week during 16 weeks at low to moderate intensity (20–70% maximal load). Only dynamic group decreased expression of 53 kDa protein, proteins from shelterin complex, oxidative stress, and improved antioxidant defense. There was no difference among groups regarding telomere length. In conclusion, dynamic resistance training was more effective than isometric in reducing markers of aging and muscle apoptosis in elderly rats. This modality should be considered as valuable tool do counteract the deleterious effects of aging.
Keywords: exercise training; telomere attrition; muscle aging; oxidative stress; antioxidant defense; apoptosis